Interaction prolonged DNA translocation through solid-state nanopores1. Issue 24 (28th June 2015) - Liang, Zexi; Tang, Zhipeng; Li, Ji; Hu, Rui; Yu, Dapeng; Zhao, Qing
<x xml:space="preserve">Abstract</x> This work strongly suggests that DNA–DNA interactions greatly impact the translocation dynamics when DNA passes through nanopores.